Alternative Opportunities for Small Farms: Peach and Nectarine Production Review - Mercy Olmstead; Jeff Williamson; Jose Chaparro; Tim Crocker (EDIS)
Florida produces some of the earliest commercial-quality peaches and nectarines in North America. During the last 10 years, many new, improved peach and nectarine cultivars have been released by the University of Florida. They have increased the potential for expansion of commercial peach and nectarine acreage throughout much of the Florida peninsula and along the Gulf Coast regions of the southeastern United States. This revised 3-page fact sheet was written by Mercy Olmstead, Jeff Williamson, Jose Chaparro, and Tim Crocker, and published by the UF Department of Horticultural Sciences, September 2011.